Gold nanoparticulate systems for new anticancer compounds delivery - Rosa, Daniela Maria Barata (2014)
My master studies have resulted in the following publication: Martins P, Rosa D, Fernandes AR, Baptista PV. 2014. Nanoparticle Drug Delivery Systems: Recent Patents and Applications in Nanomedicine. Recent Patents in Nanomedicine. 3(2):105-118.